Entrepreneurship From the Perspective of Industry 4.0: Bibliometric Analysis (Third Sector Social Economic Review, 2025)
This study was conducted to determine the extent to which entrepreneurship issues have adapted to the transformation process experienced with Industry 4.0. In this context, the levels at which Industry 4.0 and entrepreneurship issues are addressed together in academic studies were evaluated. The studies that examined Industry 4.0 alongside entrepreneurship topics were obtained from the Web of Science database. The data obtained were analysed using bibliometric analysis methods with the VOSviewer program. As of June 29, 2025, a total of 26,121 studies related to Industry 4.0 were identified in the Web of Science database, and it was determined that only 224 (0.86%) of these addressed Industry 4.0 in conjunction with entrepreneurship topics. As a result of the literature review, it was concluded that Industry 4.0 is mostly addressed in terms of its technical dimensions, while entrepreneurship and, consequently, the human element remain secondary, and there is a mismatch between the pace of development of Industry 4.0 and the rate of increase in studies on entrepreneurship. In this context, recommendations have been made for future studies to examine Industry 4.0 and entrepreneurship topics together in greater detail.
Keywords: Industry 4.0; Entrepreneurship; Management; Data; Bibliometric analysis